A practical algorithm for the treatment of mild-to-moderate atopic dermatitis (AD) in pediatric patients in Europe: expert recommendations - Matthias Augustin; Thomas Luger; Carlo Pincelli; Adam Reich; Eulàlia Baselga; Ulrich Wahn (Journal of Dermatological Treatment)
Background Atopic dermatitis (AD) is a chronic inflammatory skin condition, considered to be the most common cutaneous-related disease in children; early management in infancy with treatments of acceptable efficacy and safety has been recognized as important for outcomes.Methods An international panel of six European dermatologists and pediatric specialists was formed to discuss and develop a practical algorithm for the management of AD in pediatric patients in a European setting. The discussion combined a comprehensive review of published literature with clinical experience.Results Current guidelines recommend topical corticosteroids (TCS) as a first-line anti-inflammatory treatment for short-term AD flares, with specific recommendations for pediatric populations and sensitive areas of skin; however, due to the lack of long-term utility and associated side effects with TCS, there is a need for alternative treatments.Conclusion In this article, we propose an algorithm for a TCS-sparing treatment strategy, focusing on topical calcineurin inhibitors for the management of mild-to-moderate AD in infants and children, including AD of sensitive skin areas. This algorithm is intended as a supplementary tool to the current international and national evidence-based treatment guidelines, and to aid physicians who see and treat children with AD in their clinical practice.